An overview of the existing gap between the Romanian university educational offers focused on entrepreneurship and the maritime cruise industry - Gheorghe Militaru; Andreea Barbu; Dana C. Deselnicu; Sandra Haddad (International Business Logistics Journal)
Purpose: The purpose of this paper is to identify the existing discrepancy between the educational offers that encourage entrepreneurship and the specific requirements for the development of the maritime cruise industry in Constanta, Romania. Methodology: The authors conducted research on the university educational offers in Constanta, analyzed the specializations and training programs offered, and determined the directions for the training of professional skills within the analyzed faculties. Findings: The authors found that out of 22 faculties in Constanta, only 4 specializations focused on business management or administration. Additionally, there was a discrepancy between the skills and specializations of the personnel needed in cruise services according to the analysis of customers’ feedback on Alezzi Yacht, and the specializations offered by the Romanian educational environment. Research Implications/Limitations: The research findings suggest that there is a need for a better alignment between the educational programs and the specific requirements of the maritime cruise industry in Constanta, Romania. However, the research was limited to the educational programs in Constanta and did not consider the broader national or international context. Practical Implications/Limitations: The practical implications of the research suggest that there is a need for better training and education of personnel in the maritime cruise industry in Constanta, Romania. However, the practical limitations of the research include the need for further investigation and implementation of the suggested changes. Originality: The original contribution of this paper lies in the analysis of the existing discrepancy between the educational offers that encourage entrepreneurship and the specific requirements for the development of the maritime cruise industry in Constanta, Romania. Additionally, the case study of Alezzi Yacht provides a practical example of the challenges faced by the maritime tourism industry in the region.   Received: 18 April 2023 Accepted: 11 June 2023 Published: 15 June 2023